2021
DOI: 10.3393/ac.2020.09.03
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factor and Survival Benefit of Adjuvant Chemotherapy in Stage IIA Colon Cancer

Abstract: There is no clear evidence of the benefit of adjuvant chemotherapy (AC) in stage IIA colon cancer. Therefore, we aimed to evaluate the prognostic factors and survival benefit of AC in this disease. Methods: A retrospective data collection for patients who underwent radical surgery for colon cancer between January 2008 and December 2015 was undertaken. The cohort was divided into No AC and AC groups. Results: We included 227 patients with stage IIA colon cancer in our study cohort, including 67 and 160 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A combination of fluorouracil–oxaliplatin chemotherapy in the adjuvant setting provides a 30% relative risk reduction in disease recurrence and significantly improves overall survival (OS) [ 4 , 5 ]. While there is a consensus concerning adjuvant chemotherapy as standard treatment for stage III colon cancer, the benefits of adjuvant treatment for patients with lymph node-negative colorectal cancer remain controversial, particularly in stage IIA, which is T3N0 cancer [ 6 , 7 , 8 ]. Recent studies based on the National Cancer Database have reported on the OS benefit of adjuvant chemotherapy for patients with IIA colon cancer and high-risk prognostic features; however, the number of patients who received adjuvant chemotherapy was <50% and their performance status was not reported [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of fluorouracil–oxaliplatin chemotherapy in the adjuvant setting provides a 30% relative risk reduction in disease recurrence and significantly improves overall survival (OS) [ 4 , 5 ]. While there is a consensus concerning adjuvant chemotherapy as standard treatment for stage III colon cancer, the benefits of adjuvant treatment for patients with lymph node-negative colorectal cancer remain controversial, particularly in stage IIA, which is T3N0 cancer [ 6 , 7 , 8 ]. Recent studies based on the National Cancer Database have reported on the OS benefit of adjuvant chemotherapy for patients with IIA colon cancer and high-risk prognostic features; however, the number of patients who received adjuvant chemotherapy was <50% and their performance status was not reported [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because this study included stage II-III CRC patients, cancer status, including obstructive lesions and cancer infiltration, can influence postoperative inflammation and prognosis [41,42]. As shown in the ROC curves, the highest sensitivity of postoperative NPS compared with other scoring systems suggests that the patient's prognosis is influenced by multidisciplinary aspects of the biology of the primary tumor, the patient's nutritional status, and adequate postoperative management [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The number of retrieved lymph nodes, which has a significant impact on long-term oncological outcomes in advanced colorectal cancer, is important in achieving radical lymph node dissection. Lymph node dissection extent is of practical interest to colorectal surgeons [1][2][3]. The Japanese Society for Cancer of the Colon and Rectum (JSCCR) guidelines recommend D3 lymph node dissection for stage II and III colorectal cancers, and D2 dissection for early-stage disease [4].…”
Section: Introductionmentioning
confidence: 99%